In vivo fertilising ability of frozen-thawed boar sperm treated with cholesterol-loaded cyclodextrins prior to cryopreservation - Tomás, Cristina; Blanch, Eva; Cebrián, Begoña; Mocé, Eva (2017)
The use of frozen-thawed (FT) sperm for the artificial insemination of pigs is rare. Treating boar sperm with cholesterol-loaded cyclodextrins (CLC) prior to cryopreservation enhances the penetration of immature oocytes in vitro, and this phenomenon has been positively correlated with in vivo fertilisation ability in pigs. The objective of this study was to compare the in vivo fertilising ability of boar sperm treated with 0 (control) or 1 mg CLC/120 x 106 sperm (CLC) prior to freezing. The fertilising ability of the FT sperm was compared in hormonally treated (equine/human chorionic gonadotropin hormones; eCG/hCG) weaned sows inseminated once (cervical insemination) at the following fixed-times after hCG administration: 37 h (experiment 1) or 30 h (experiment 2). In experiment 1, both treatments exhibited similar fertility rates of 67.7 and 55.9% for the control and CLC, respectively (P>0.05); however, the CLC group had a smaller litter size (11.3 +/- 0.9) than the control group (13.6 +/- 0.8) (P0.05) for both treatments. These results indicate that the timing of insemination developed for the FT control sperm may not be suitable for CLC-treated sperm and that CLC-treated sperm may benefit from a shorter time interval between the hCG treatment and insemination. Moreover, acceptable results can be obtained with FT boar sperm with a single artificial insemination performed 30 h after hCG treatment, which is the time interval recommended for fresh sperm. (C) 2013 Elsevier B.V. All rights reserved.